Pneumococcal Serotype Identification by Capsular Sequence Typing (CST): A Modified Novel Approach for Serotyping Directly in Clinical Samples - Nektarios Marmaras; Athanasia Xirogianni; Anastasia Papandreou; Efthymia Petinaki; Vana Papaevangelou; Maria Tsolia; Georgina Tzanakaki (Diagnostics, 2021)
As almost 60–70% of Invasive Pneumococcal Disease (IPD) is identified by nonculture methods in Greece, serotyping is of high importance for the better monitoring of pneumococcal serotypes due to the availability of conjugate vaccines. The aim of the study was the modification and direct application of the Capsular Sequence Typing (CST) assay in clinical samples in order to serotype Streptococcus pneumoniae culture-negative, Polymerase Chain Reaction (PCR_-positive samples, followed by CST group specific single-tube PCR assays. A two-step PCR modified assay was applied on a total of 306 samples (such as CSF, blood, pleural and middle ear fluids, isolates) obtained from 283 patients with IPD. The overall performance permits a rapid, accurate and cost-effective method for nonculture pneumococcal serotyping. As the management of IPD is closely related to the continuous monitoring of pneumococcal serotypes, the proposed approach proved to be a valuable tool for the typing and epidemiological monitoring of S. pneumoniae, for the evaluation of the overall impact of vaccination programs in the era of pneumococcal conjugate vaccines, in order to initiate the appropriate vaccination strategy.